The Best Practice of Internal Supervision of the Schools Under the Samut Prakan Primary Educational Service Area Office 1 - Benkoon , Sureerat; Noichan, Nantiya (The Journal of Development Administration Research, 2020)
The objectives of this research were to 1) study the state of internal supervision of the schools under the Samut Prakan primary educational service area office 1. And 2) determine the good practice of internal supervision of the schools under the Samut Prakan primary educational service area office 1. It was a quantitative research. The sample was 322 administrators and teachers of the schools under the Samut Prakan primary educational service area office 1. The tools used were questionnaires and interviews with experts to find good practice in school internal supervision. Collect data and statistics used to analyze data such as percentage, average and standard deviation. Seven experts were interviewed to determine good practices of internal supervision of the schools. The research found that 1) The state of internal supervision: overall internal supervision of schools was at a high level. When individual aspects were considered, an aspect with the highest mean score was direct assistance to teachers, followed by professional development, group work skills, terms curriculum development and aspect with the lowest mean score of classroom action research. 2) The results of determining best practice of internal supervision of schools, there are 5 aspects as follows: 1) in terms of direct assistance to teachers, preparing a PLC, organizing monthly meeting to exchange knowledge and learning. An administrator should act as a supervisor by him/herself to meet step-by-step process. 2) in terms of professional development, the sample schools provided practical guidelines for enhancing knowledge and understanding to morally and ethically practice according to teaching professional standards and professional progress. 3) in terms of group work skills, there should prepare PLC, organize ice breaking, group-relations and support teamwork 4) in terms curriculum development, should be prepared in a clear preparation process. The core curriculum must be based on with the interference of the actual state of the locality. The course implementation was evaluated along with the preparation of the learning plan. and 5) in terms of classroom action research, schools should prepare and integrate classroom action research to its own annual operational plan in order to set the budget appropriately.